Do you really need that pill? : how to avoid side effects, interactions, and other dangers of over medication - Jacobs, Jennifer (Skyhorse Publishing, 2018)
"A silent epidemic in the United States is imperiling our health and threatens to bankrupt our health care system: over medication. Today, one-third of all adults take two or more prescription drugs, and half of all seniors take more than five daily. This book the first of its kind that tackles the epidemic overuse of prescription drugs. The first half of the book describes the dangers of taking too many drugs, including drug interactions, medication errors, unintentional overdoses, unnecessary medications, made-up illnesses (“restless leg syndrome”), and side effects that actually mimic a new illness. The second half discusses the benefits and harms caused by many of the most popular drugs used to treat diseases, such as high blood pressure, diabetes, high cholesterol, acid reflux, depression, and pain. It tells which drugs are really needed and whether or not they cause side effects. Finally, readers will learn: how to discuss their concerns about too many medications with their health care providers, simple ways to make positive lifestyle changes, and when to consider alternative healing approaches. Combining stories of those who have suffered ill effects from taking too many drugs with data from cutting-edge medical findings, Do You Really Need That Pill? helps readers realize they can choose different solutions to their health problems."--